USING OF TRIPLE-TREATED WASTEWATER IN AGRICULTURAL IRRIGATION IN AL-AHSA OASIS, SAUDI ARABIA. - El-Sebaei, M. N.; Osman, R. T.; Mansour, H. E.H.; Al-Asmari, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The agricultural sector consumes about 84% of the total actual water consumption annually in Kingdom of Saudi Arabia, therefore, the research depends on questionnaire data that was judged before being used in the study of a random sample of 355 farms from Al-Ahsa Oasis which irrigated with two types of water (groundwater, triple-treated wastewater) to measure the economic impact of the using of triple-treated wastewater in irrigating palm and lemon crops, the results indicated a statistically significant correlation between the extent of farmers'  which using of triple treated wastewater in irrigation and all of: size of the tenure, family size and the educational level of the farmer. While the relationship was negative with all of: age of the farmer, and number of years of his experience. The results showed that the productivity of dunums on farms irrigated with triple-treated wastewater increased by 0.32, 0.30, 0.22 tons, representing about 19.2%, 17.2%, 16.8% compared to which using groundwater for Alkhallas palm, Alrziz palm and lemon.